PERBANDINGAN MODEL LATIHAN PEREGANGAN STATIS DAN DINAMIS TERHADAP FLEKSIBILITAS - Aditya Permana Putra; Sudirman Husin; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2015)
This study aims to determine how big the model comparison exercise static stretching and dynamic stretching models and models which are more effective exercises for flexibility. Methodology used in this study is experimental data analysis of the results of the initial test and final test model of static stretching and dynamic stretching exercises models using a single variance analysis technique. In the model of static stretching exercises come tcount 8.765 ttable = 2.042 which means rejected (H0) so no influence model of static stretching exercises. In the model of dynamic stretching exercises come tcount 3,041 ttable = 2.042, then reject the null hypothesis (H0) that there was an effect of stretching models dynamic. While the analysis of the final test model group differences static stretching exercises and stretching exercises dynamic models obtained tcount 3,041 ttable = 2.042 so that there are differences between groups of models of static and dynamic stretching exercises for flexibilityPenelitian ini bertujuan untuk mengetahui seberapa besar perbandingan model latihan peregangan statis dan model peregangan dinamis serta model latihan mana yang lebih efektif terhadap fleksibilitas. Metodologis yang digunakan dalam penelitian ini adalah eksperimen teknik analisis data dari hasil tes awal dan tes akhir model latihan peregangan statis dan model latihan peregangan dinamis menggunakan teknik analisa varians tunggal. Pada model latihan peregangan statis didapat thitung 8,765 ttabel = 2,042 yang berarti tolak ( H0 ) sehingga ada pengaruh model latihan peregangan statis. Pada model latihan peregangan dinamis didapat thitung 3,041 ttabel = 2,042 maka tolak hipotesis nol ( H0 ) sehingga ada pengaruh model peregangan dimanis. Pada analisis perbedaan tes akhir kelompok model latihan peregangan statis dan model latihan peregangan dinamis didapat thitung 3,041 ttabel = 2,042 sehingga ada perbedaan yang antara kelompok model latihan peregangan statis dan dinamis terhadap fleksibilitasKata kunci:dinamis, feksibilitas, pergangan statis.